CREATING JUSTICE AND LAW THROUGH THE JUXTAPOSITION OF THE PRESENTATIONS OF ODYSSEUS AND THE SUITORS - Kaluđerović , Željko (Glasnik Advokatske komore Vojvodine, 2020)
In the paper the author analyzes Homer’s specific presenting of justice, primarily from the perspective of his Odyssey. In this epic we can identify an additional dimension of justice, beside in the previous essay mentioned characteristics of equivalence and correlativity, and the principle "might is right", which is an implication of its application to inter polis relations. In addition, we should add the place that belongs to Zeus, through which Hellenes should comprehend that the justice is necessary for the resolution of their conflicts. As the highest representative of justice in general, Zeus panishes those whose acts are not in compliance with justice, and which, finally, tells the Acheans that they should establish a community founded on justice, and that community is polis.